PCR Amplification and Phylogenetic Analysis of groESL Operon Sequences from Ehrlichia ewingii and Ehrlichia muris - Sumner, John W.; Storch, Gregory A.; Buller, Richard S.; Liddell, Allison M.; Stockham, Steven L.; Rikihisa, Yasuko; Messenger, Sharon; Paddock, Christopher D. (Journal of clinical microbiology, 2000)
Broad-range PCR primers were used to amplify part of the groESL operon of the canine pathogen Ehrlichia ewingii , recently recognized as a human pathogen, and the murine pathogen Ehrlichia muris . Phylogenetic analysis supported the relationships among Ehrlichia species previously determined by comparison of 16S rRNA gene sequences. These sequences provide additional PCR targets for species for which few gene sequences have been determined.